2009
DOI: 10.1590/s1413-78522009000300005
|View full text |Cite
|
Sign up to set email alerts
|

Análise cinemática do joelho ao subir e descer escada na instabilidade patelofemoral

Abstract: OBJETIVO: Analisar e identificar possíveis adaptações da marcha em indivíduos com diagnóstico de instabilidade patelofemoral objetiva, durante a atividade de subida e descida de escada. MÉTODOS: Foram analisados um grupo controle (grupo A), composto por 9 mulheres com média de idade de 25 anos (±1,87), média de altura de 1,62m (±0,05) e média de peso de 56,20kg (±7,34); e, um grupo de 9 mulheres com instabilidade patelofemoral objetiva (grupo B), média de idade de 24 anos (±6,02), média de altura de 1,62m (±0,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 13 publications
(20 reference statements)
0
4
0
1
Order By: Relevance
“…Estratégias adaptativas para diminuir a sobrecarga na articulação patelofemoral, como menor flexão de joelhos, redução da cadência e velocidade na subida e descida de escadas, também são citadas na literatura como forma de controlar o quadro agudo de dor. 30 Com relação às estratégias adaptativas para execução do exercício de agachamento, 71,43% das voluntárias com dor patelofemoral mencionaram redução da amplitude de movimento e/ou da carga utilizada para a execução do exercício, a fim de evitar outro quadro álgico agudo.…”
Section: Discussionunclassified
“…Estratégias adaptativas para diminuir a sobrecarga na articulação patelofemoral, como menor flexão de joelhos, redução da cadência e velocidade na subida e descida de escadas, também são citadas na literatura como forma de controlar o quadro agudo de dor. 30 Com relação às estratégias adaptativas para execução do exercício de agachamento, 71,43% das voluntárias com dor patelofemoral mencionaram redução da amplitude de movimento e/ou da carga utilizada para a execução do exercício, a fim de evitar outro quadro álgico agudo.…”
Section: Discussionunclassified
“…Several studies have reported that subjects with PFPS adopt different strategies, such as lower knee flexion angle, reduction in the knee extensor moment and in ground reaction forces, in addition to reduction in gait speed and rhythm during functional activities to avoid or reduce their pain levels 6,[9][10][11]13,14,32 . In our study, we initially hypothesized that subjects with PFPS could change their walking patterns as a strategy for reducing pain during the performance of functional activities, and this could lead to changes in plantar pressure distribution, reducing contact time and peak pressures of the member with pain in relation to the dominant member of the control group.…”
Section: Discussionmentioning
confidence: 99%
“…Its signs and symptoms are exacerbated mainly during the performance functional activities, among which we can highlight movements for climbing up and down stairs and sloping surfaces 6,7 . In this sense, some studies were conducted to investigate biomechanical patterns adopted by subjects with PFPS during the performance of functional activities, noting changes in the electromyographic activity of vastus 8 , in ground reaction forces 9 , in kinematics 7,[9][10][11][12][13][14][15][16] , and in plantar pressure distribution 17,18,2 . According to Thijs et al 2 , changes in plantar pressure distribution can reduce the shock absorption ability of the foot, transferring part of the ground reaction force to more proximal joints, including the knee, resulting in overload of the patellofemoral joint with consequent increase in patellofemoral pain.…”
Section: Introductionmentioning
confidence: 99%
“…However, not only a decrease in the strength of knee flexors and extensors may lead to alterations in functionality 33 ; the adoption of coping strategies during the performance of functional activities with the purpose of reducing or avoiding pain might also lead to long-term reduced strength in individuals with PFPS 15,19 . Among these strategies, we highlight the reduction of the knee's flex angle, an alteration observed in several studies 11,27,34 which has the purpose of reducing stress and patellofemoral pain, but might incur harmful effects in the future, causing quadriceps atrophy and weakness 19 . However, caution is necessary, considering that we did not conduct cinematic evaluation during the performance of functional activities, which would verify the occurrence or non occurrence of these findings in the individuals involved in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Its etiology is multifactorial, and the most accepted hypothesis for its development is poor patellar alignment 2,3,6 . However, other factors may also contribute to the onset or worsening of PFPS, such as quadriceps weakness 2 , alterations in the postural alignment of lower limbs, especially related to hind foot and Q angles 7 , and abnormalities in the biomechanics of lower extremities, such as subtalar excessive eversion 8 , smaller angle of knee flexion 11,12 , weak hip muscles 13 , in addition to excessive hip adduction and internal rotation 14 . The signs and symptoms of this syndrome are exacerbated especially during the performance of functional activities, among which we highlight the movements of going up and down the stairs and inclined surfaces 15,16 , which could result in the modification of locomotive patterns.…”
Section: Introductionmentioning
confidence: 99%